Cannabis Use and Car Crashes: A Review - Preuss, Ulrich W.; Huestis, Marilyn A.; Schneider, Miriam; Hermann, Derik; Lutz, Beat; Hasan, Alkomiet; Kambeitz, Joseph; Wong, Jessica W. M.; Hoch, Eva (Frontiers in Psychiatry, 2021)
In this narrative review, state-of-the-art evidence on the relationship between cannabis use, traffic crash risks and driving safety were analyzed. Systematic reviews, meta-analyses and other relevant papers published within the last decade were systematically searched and synthesized. Findings show that meta-analyses and culpability studies consistently indicate an increased risk of crashes after acute cannabis use. These risks vary across included study type, crash severity and method of substance application and measurement. Some studies show a correlation between high THC blood concentrations and car crash risk while most studies do not support this relationship at lower concentrations. However, no scientifically supported clear cut-off concentration can be derived from these results. Further research is needed to determine dose-response effects on driving skills combined with measures of neuropsychological functioning related to driving skills and crash risk.